Same Invasion, Different Routes: Helminth Assemblages May Favor the Invasion Success of the House Mouse in Senegal - Diagne, Christophe; Granjon, Laurent; Tatard, Caroline; Ribas, Alexis; Ndiaye, Arame; Kane, Mamadou; Niang, Youssoupha; Brouat, Carine (Frontiers in Veterinary Science, 2021)
Previous field-based studies have evidenced patterns in gastrointestinal helminth (GIH) assemblages of rodent communities that are consistent with “enemy release” and “spill-back hypotheses, suggesting a role of parasites in the ongoing invasion success of the exotic house mouse (Mus musculus domesticus) in Senegal (West Africa). However, these findings came from a single invasion route, thus preventing to ascertain that they did not result from stochastic and/or selective processes that could differ across invasion pathways. In the present study, we investigated the distribution of rodent communities and their GIH assemblages in three distinct zones of Northern Senegal, which corresponded to independent house mouse invasion fronts. Our findings first showed an unexpectedly rapid spread of the house mouse, which reached even remote areas where native species would have been expected to dominate the rodent communities. They also strengthened previous insights suggesting a role of helminths in the invasion success of the house mouse, such as: (i) low infestation rates of invading mice by the exotic nematode Aspiculuris tetraptera at invasion fronts – except in a single zone where the establishment of the house mouse could be older than initially thought –, which was consistent with the ‘enemy release’ hypothesis; and (ii) higher infection rates by the local cestode Mathevotaenia symmetrica in native rodents with long co-existence history with invasive mice, bringing support to the ‘spill-back’ hypothesis. Therefore, ‘enemy release’ and ‘spill-back’ mechanisms should be seriously considered when explaining the invasion success of the house mouse – provided further experimental work demonstrate that involved GIHs affect rodent fitness and/or exert selective pressures. Next steps should also include evolutionary, immunological and behavioral perspectives to fully capture the complexity, causes and consequences of GIH variations along these invasion routes.